The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1111/jsm.12938
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, Regional Characteristics, Knowledge, and Attitude Toward Female Genital Mutilation/Cutting in Southern Iran

Abstract: Introduction Female genital mutilation/cutting (FGM/C), also known as female circumcision, is an ancient traditional procedure that involves partial or total removal of the female external genitalia for nonmedical reasons. Although it is well described in African and some Arabic countries, data from Iran are scarce. Aim To describe the epidemiology, regional characteristics, knowledge, and attitude toward FGM/C in Southern Ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
23
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 25 publications
(62 reference statements)
6
23
5
Order By: Relevance
“…In some traditional societies, FGM/C is a requirement for getting married so it is not surprising that FGM/C is more common among older married than among unmarried women . Consistent with other studies , FGM/C was more common in older age groups, which shows the decline in the practice among younger generations. Preventive work both in Finland and in the countries of origin are also likely to have had some effect.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In some traditional societies, FGM/C is a requirement for getting married so it is not surprising that FGM/C is more common among older married than among unmarried women . Consistent with other studies , FGM/C was more common in older age groups, which shows the decline in the practice among younger generations. Preventive work both in Finland and in the countries of origin are also likely to have had some effect.…”
Section: Discussionsupporting
confidence: 75%
“…FGM/C prevalence is known to be high among Somalis . However, there is little information on the tradition of FGM/C among Kurdish women, though it is known that in Iraqi Kurdistan, the prevalence of FGM/C is between 40 and 70 percent . In Finland, the Ministry of Social Affairs and Health has published a specific action plan on the prevention of FGM/C for the years 2012–2016 .…”
mentioning
confidence: 99%
“…The study revealed a FGM prevalence of 30.3% among female students of selected primary and secondary schools in Karari locality of Khartoum state, which was lower when compared to the prevalence documented by Sudan multiple indicator cluster survey (86.6%) (4). This result was also lower than the FGM prevalence reported by other studies, for example in rural areas of Nigeria (49.6%) (13), nationwide in Sierra Leone (94%) (14), in selected areas of eastern Ethiopia (90%) where Muslims make up 84% of the study participants (15), and in Hormozgan in the southern region of Iran (68.5%) where Muslims form all study participants (16). However, this lower result might be due to reticence by females at this age to give such information, even with assurances of anonymity.…”
Section: Discussioncontrasting
confidence: 57%
“…[4] It may also be seen among some ethnic groups and immigrants living in developed European and North American countries and Australia. [5] Although there are no o cial and comprehensive statistics on the prevalence of FGM/C in Iran, the results of few studies have shown that the prevalence of the practice varies by region and is mainly concentrated in the western and southwestern provinces (Hormozgan, Khuzestan, Bushehr, Kurdistan, and Kermanshah [6][7][8] which are mostly inhabited by Sunni Muslims. The prevalence of the FGM/C is reported to be between 55.5 and 70% primarily in rural of these areas.…”
Section: Introductionmentioning
confidence: 99%
“…[11] Some studies have shown that the main reasons for performing this practice in Iran are the preservation of traditions, cleanliness, religious recommendations, and control of sexual desire, respectively. [8,9] These factors have turned FGM/C, as an element for inequality and violence against women, into a social norm or conviction.…”
Section: Introductionmentioning
confidence: 99%